KOMBINASI METODE HUNGARIAN DAN PERMUTASI UNTUK PENDUKUNG KEPUTUSAN PENUGASANDEPARTEMEN DAN KOORDINATOR DIVISI: KOMBINASI METODE HUNGARIAN DAN PERMUTASI UNTUK PENDUKUNG KEPUTUSAN PENUGASANDEPARTEMEN DAN KOORDINATOR DIVISI - Dina Maulina; Muhamad Rahmat Jatnika (Institute of Computer Science (IOCS), 2019)
In overcoming the problem of division of labor, commercial applications so far can only provide one solution and cannot handle the assessment process which has several criteria in it, for example Microsoft Excel and WinQSB. The limitations of commercial applications have been overcome in previous studies, but still have two disadvantages, namely the number of assignments and duty bearers must be the same and have not involved sub-criteria of assessment. By overcoming these two shortcomings, assignment cases that can be handled are more in line with the reality that often occurs. The method used to overcome the assignment problem in the application is the Hungarian method and permutation. The study was carried out using the waterfall method of the System Development Life Cycle (SDLC) model. With the creation of this new assignment application, the solution given to decision makers can amount to more than one choice if possible, with the number of tasks that can differ from the number of duty bearers. In addition, the assignment application can also produce a comprehensive task sharing solution because it is able to handle task assessments that have criteria and subcriteria within them.